2018
DOI: 10.1242/bio.035196
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications by polyphenolic compounds alter gene expression in the hippocampus

Abstract: In this study, we developed an experimental protocol leveraging enhanced reduced representation bisulphite sequencing to investigate methylation and gene expression patterns in the hippocampus in response to polyphenolic compounds. We report that the administration of a standardized bioavailable polyphenolic preparation (BDPP) differentially influences methylated cytosine patterns in introns, UTR and exons in hippocampal genes. We subsequently established that dietary BDPP-mediated changes in methylation influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…These epigenetic marks have been described as essential for hippocampal synaptic plasticity, cognitive function [ 46 ], and age-related modifications [ 47 ]. In line with our results, several studies found that dietary polyphenols alter epigenetic mechanisms by changing 5-mC levels [ 48 ] or regulating the gene expression or enzymatic activity of DNMTs and TETs [ 49 ]. In addition, recent studies suggest that maternal resveratrol intake after different stimuli can have a significant influence on the susceptibility of the offspring to age-related diseases including cognitive decline [ 44 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…These epigenetic marks have been described as essential for hippocampal synaptic plasticity, cognitive function [ 46 ], and age-related modifications [ 47 ]. In line with our results, several studies found that dietary polyphenols alter epigenetic mechanisms by changing 5-mC levels [ 48 ] or regulating the gene expression or enzymatic activity of DNMTs and TETs [ 49 ]. In addition, recent studies suggest that maternal resveratrol intake after different stimuli can have a significant influence on the susceptibility of the offspring to age-related diseases including cognitive decline [ 44 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…The current study and others assessed body weight as an important indicator for the general health of the animals, which is also one of the important parameters for the clinical observations in the toxicity test [51]. We previously treated mice for 4 [52, 53] to 6 weeks [26] with a dose of 783 mg/kg BW/day BDPP polyphenols. In comparison to control, vehicle-treated mice, we observed no difference in BW gain [26, 52, 53], food consumption [26, 52, 53], water consumption [26, 52, 53] or normal grooming behavior [26].…”
Section: Discussionmentioning
confidence: 99%
“…We previously treated mice for 4 [52, 53] to 6 weeks [26] with a dose of 783 mg/kg BW/day BDPP polyphenols. In comparison to control, vehicle-treated mice, we observed no difference in BW gain [26, 52, 53], food consumption [26, 52, 53], water consumption [26, 52, 53] or normal grooming behavior [26]. Based on a drug equivalent dose conversion criterion that takes into consideration body surface area [rat equivalent dose in mg/kg = mouse dose in mg/kg x (mouse wt in kg / rat wt in kg) 0.33 ] [54], the mouse dose is equivalent to a dose of 325.6 mg/kg BW/day BDPP polyphenol for a 500 gm rat.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that P. agglomerans C1 has genes encoding enzymes (e.g., a CAT-catalase, ec 1.11.1.6) that are involved in the biosynthesis of cinnamic-related compounds from intermediates of the tryptophan pathway, and we have evidence that strain C1 produces cinnamates as well as peptides and cyclopeptides that can crosstalk with auxin ( Luziatelli et al, 2020b ). These compounds may likely play a possible regulative role in plant gene expression through epigenetic mechanisms, such as DNA methylation, histone modification (acetylation, methylation, and phosphorylation), and miRNA activation, as it already emerged in humans ( Zhu et al, 2016 ; Frolinger et al 2018 ; Arora et al, 2019 ; Carlos-Reyes et al, 2019 ; Patnaik and Anupriya, 2019 ). These mechanisms likely activate many regulatory pathways generating a response, in parallel to the pathway activated by auxin compounds, and thus establish a synergistic action.…”
Section: Discussionmentioning
confidence: 99%